In-Depth Analysis of Malaysia International Trade Pattern - Abdul Aziz Lai; Imbarine Bujang (International Journal of Supply Chain Management, 2017)
2015 wave a challenging year for Malaysia in terms of economic as well as international trade due to several factors inter alia plummeting of global crude oil prices, Ringgit depreciation and sluggish of Asian giants trading momentum suchlike Peoples Republic of China (MITI Annual Report, 2015). Nevertheless, Malaysia trade still managed to push beyond the gauge projected by World Bank and International Monetary Funds (IMF) which recorded 5% growth than expected 4.7%. Despite exceeding the projection by 0.3%, the actual trade level recorded slightly dropped compared to 2014, therefore it is a vital need for Malaysia to restructure the movement of export and import to ensure consistent performance in the future. This study analyses top 60 Malaysia trading partners worldwide by taking into consideration the economic as well as financial determinants of trade. Rather than just a clich linear regression, this study differs from others by segregating the top 60 partners into three level of segregation together with the prominent gravity model of trade to identify the superior and profitable trading partners categories Malaysia should focus with. Lastly, the augmented gravity model of static panel analysis results shows mixed findings in which Malaysia trade with different segregation level provides different patterns and determinants of trade.